Follicular output rate tends to improve clinical pregnancy outcomes in patients with polycystic ovary syndrome undergoing in vitro fertilization-embryo transfer treatment. Issue 10 (October 2019) - Tan, Xiaoqing; Wen, Yu; Chen, Huixiao; Zhang, Ling; Wang, Bin; Wen, Hongwei; Zhang, Fengli; Wu, Qin; Du, Jing
Objective: This study aimed to examine the relationship between the follicular output rate (FORT) and clinical outcomes in patients with polycystic ovarian syndrome (PCOS). Methods: A total of 841 patients with PCOS undergoing in vitro fertilization-embryo transfer (IVF-ET) were divided into three groups according to their FORT (low, middle, and high). Controlled ovarian hyperstimulation and clinical outcomes were compared retrospectively. Results: Serum estradiol levels on the day of human chorionic gonadotropin (3780.5, 3599.9, and 3375.7 pg/mL) and the number of retrieved oocytes (17.5, 16.1, and 14.8) decreased from the high to low FORT groups. Pre-ovulatory follicle counts were significantly higher in the high FORT group than in the middle and low FORT groups. The number of retrieved oocytes, high-quality embryo rate, and clinical pregnancy rate decreased from the high to low FORT groups. The incidence of moderate and severe ovarian hyperstimulation syndrome (OHSS) in the middle FORT group was significantly lower than that in the high and low FORT groups. Conclusions: FORT may be used to predict clinical outcomes of IVF/intracytoplasmic sperm injection-embryo transfer in patients with PCOS. Efforts should be made to prevent OHSS in patients with PCOS and a high or low FORT in controlled ovarian hyperstimulation cycles.